A new classification for septal perforation and effects of treatment methods on quality of life - Sapmaz,Emrah (2019)
Abstract Introduction: Septal perforation is a condition characterized by loss of cartilage and/or bony structures along with the mucoperichondrium and mucoperiosteum lining them. The etiology includes a history of nasal surgery or trauma, nose picking, bilateral septal cauterization, overuse of nasal sprays, cocaine abuse, vasculitis, and malignancies. Objective: Comparison of quality of life in patients with septal perforation after conservative or surgical treatment, and a new approach for the determination of the diameter of the perforation from a different point of view. Methods: The diameter of septal perforation, total vertical diameter of septum, and horizontal diameter of the perforation were measured in a total of 34 patients. Nineteen of the patients underwent surgical septal perforation repair, and 15 of them received septal button application. The patients were asked to complete the Glasgow Benefit Inventory quality of life questionnaire. Results: The septal perforation successfully healed in 18 of 19 patients who underwent surgical treatment. The quality of life scores were statistically significantly higher in the surgical treatment group when compared to the button group (p < 0.05). Conclusion: The septal perforation classification we propose would be beneficial for providing realistic dimensions, treatment methods, and surgical techniques.